2021
DOI: 10.1101/2021.10.31.466372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic inhibition of the Plasmodium apicoplast decreases haemoglobin degradation and antagonises dihydroartemisinin action

Abstract: The World Health Organisation (WHO) recommends artemisinin (ART) combinations for treatment of uncomplicated Plasmodium falciparum malaria. Understanding the interaction between co-administered drugs within combination therapies is clinically important to prevent unintended consequences. The WHO guidelines recommend second line treatments that combine artesunate with tetracycline, doxycycline, or clindamycin—antibiotics that target the Plasmodium relict plastid, the apicoplast. In addition, antibiotics can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 60 publications
(88 reference statements)
3
8
0
Order By: Relevance
“…Our finding that C3 antagonizes ART is in line with a recent report that other apicoplast−targeting antimalarials also antagonize ART [31]. These findings caution against the use of ART partner drugs that inhibit the Fd−FNR interaction and other apicoplast targets, which may reduce ART efficacy in malaria chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our finding that C3 antagonizes ART is in line with a recent report that other apicoplast−targeting antimalarials also antagonize ART [31]. These findings caution against the use of ART partner drugs that inhibit the Fd−FNR interaction and other apicoplast targets, which may reduce ART efficacy in malaria chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…The interactions between DHA and the test compounds were assessed as the fractional inhibition concentration (□FIC) index, and the mean □FICs of the combinations were compared between fd wild-type (fd WT ) and fd -mutated (fd MT ) parasites using Welch’s T-test (Figure 3). An antagonistic effect was indicated when □FIC >1.1, an additive effect was indicated when 0.9 < □FIC < 1.1, and synergism was indicated when □FIC< 0.9, using the criteria established by previous studies of antimalarial interactions [31,32]. For the DHA and C3 combinations, the mean □FICs were moderately antagonistic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the key antimalarial artemisinin is potentiated by parasite haem digestion (Pandey et al, 1999 ), but Kennedy et al showed that haem digestion is perturbed by common apicoplast inhibitors (Kennedy et al, 2019 ), which begs the question of whether apicoplast inhibitors might be antagonistic to artemisinin, and indeed any derivatives of artemisinin requiring activation by haem digestion. Early indications are that doxycycline—a widely used, apicoplast targeting antimalarial (Dahl et al, 2006 ; Goodman et al, 2007 )—is indeed antagonistic to artemisinin because it impedes haem digestion and thereby blunts the impact of artemisinin (Crisafulli et al, 2021 ).…”
Section: The Apicoplast During Blood Stages—some Updatesmentioning
confidence: 99%